Torchwood. The complete first season [videorecording (DVD)] - Kelly, Brian (Television director); Teague, Colin; Strong, James (Television director); Troughton, Alice; Way, Ashley; Barrowman, John, 1967-; Myles, Eve, 1978-; Gorman, Burn, 1974-; Mori, Naoko, 1975-; David-Lloyd, Gareth, 1981- (BBC Video : Distributed by BBC Worldwide Americas ; Distributed in the USA and Canada by Warner Home Video, 2008)
Led by Captain Jack Harkness, the Torchwood team delves into the unknown and fights the impossible. From an underground base built on a rift in time and space, the team responds to any alien threat-- a meteorite crash landing, sightings of extra-terrestrial technology, an unusual autopsy report, the spread of a deadly alien virus. Everyone who works for Torchwood is under 35. Some day that's because it's a new science-- others say it's because they die young--Container.